Social Assessment Helps Sharpen Sector Reforms in Armenia - World Bank (World Bank, Washington, DC, 2012)
Armenia's recent experience underscores the value of using social assessment (SA) in social sector reform projects. The Government of Armenia and the World Bank carried out an SA to evaluate the social and institutional feasibility of the government's proposed education and health sector reforms. The social assessment helped to identify key stakeholders and their expectations and attitudes toward health and education reforms; test compatibility of beneficiaries' stated needs and the proposed reforms; adjust proposed project components to meet beneficiary needs and reflect socioeconomic realities; and collect and organize baseline data for ongoing participatory monitoring.